Die steel and dies
The mold steel with optimized composition and heat treatment achieves high hardness and thermal conductivity, addressing wear and seizure issues in high-temperature processing.
Patent Information
- Application Number
- JP2020172572
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-03
- Filing Date
- 2020-10-13
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-10-13
AI Technical Summary
Existing mold steels face challenges with low softening resistance, low thermal conductivity, and high thermal expansion, leading to wear and seizure during high-temperature processing such as die casting, hot stamping, and tailored die quenching.
A mold steel composition with controlled amounts of C, Si, Mn, Cr, Mo+W/2, V, and N, optimized for high initial hardness, fine (Mo,W) carbides, and high thermal conductivity, achieved through specific quenching and tempering processes.
The solution provides mold steels with enhanced softening resistance, high initial hardness, and improved thermal conductivity, reducing wear and seizure, and shortening cycle times in high-temperature processing.
Smart Images

Figure 0007608772000003 
Figure 0007608772000004 
Figure 0007608772000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a die steel and a die, and more particularly to a die steel exhibiting high softening resistance, and a die using such a die steel. [Background technology]
[0002] "Die casting" refers to a casting method for producing castings with high dimensional accuracy by forcing molten metal into a mold. Die casting is used to produce castings made of metals with relatively low melting points (e.g., Al, Zn, Mg, or alloys thereof).
[0003] "Hot stamping" is a forming method in which a plate material heated to a high temperature is press-formed using a die, and the plate material is quenched (hardened) in a die cooled with cooling water at the same time. Hot stamping is used for press forming of steel plates that have low cold formability and large springback (e.g. ultra-high tensile steel plates).
[0004] "Tailored die quenching" refers to a forming method in which a plate material heated to a high temperature is press-formed using a die whose design surface is partially heated by a heat source, and the plate material is partially quenched (hardened) at the design surface, which is maintained at a low temperature, while the plate material is being formed. Tailored die quenching is used in the press forming of parts that require strength distribution (for example, parts that make up the frame of an automobile).
[0005] In processes for processing high-temperature workpieces, such as die casting, hot stamping, and tailored die quenching, dies are subjected to thermal cycles during use, and therefore require high softening resistance and heat check resistance.
[0006] In order to solve this problem, various proposals have been made in the past. For example, Patent Document 1 states: (a) In mass%, it contains C: 0.30-0.45%, Si: more than 0.3-1.0%, Mn: 0.6-1.5%, Ni: 0.6-1.8%, Cr: 1.4-less than 2.0%, Mo+W / 2: more than 1.0-1.8%, V+Nb / 2: 0.2% or less, and the balance is Fe and unavoidable impurities; (b) A specific relationship holds between each component A high toughness hot work tool steel is disclosed.
[0007] The same document states: (A) The softening resistance is improved by optimizing the balance of each component. (B) By setting the N content to 0.015 mass% or less, the formation of coarse carbonitrides is suppressed, improving toughness; and (C) Optimizing the size of carbides and the number of carbides per unit area improves machinability and softening resistance. is stated.
[0008] In Patent Document 2, (a) In mass%, C: 0.34-0.40%, Si: 0.3-0.5%, Mn: 0.45-0.75%, Ni: 0-less than 0.5%, Cr: 4.9-5.5%, Mo and W are either alone or in combination (Mo+1 / 2W): 2.5-2.9%, V: 0.5-0.7%, with the balance being Fe and unavoidable impurities; (b) The cross-sectional structure at the time of quenching includes a blocky structure and an acicular structure, with the blocky structure (A%) being 45 area % or less, the acicular structure (B%) being 40 area % or less, and the retained austenite (C%) being 5 to 20 volume %. A hot work tool steel is disclosed.
[0009] The same document states: (A) The structure after quenching has a large effect on toughness and high-temperature strength. (B) In order to suppress the deterioration of toughness, it is preferable to reduce the area ratio of the blocky structure and the acicular structure to a predetermined value or less, and (C) To prevent deterioration of strength characteristics, the less retained austenite, the better, but retaining an appropriate amount of austenite improves toughness. is stated.
[0010] Patent Document 3 states: (a) by weight percent, C: 0.25-0.55%, Si: 1.2% or less, Mn: 1.5% or less, Ni: 2.0% or less, Cr: 6.0-8.0%, 1 / 2W+Mo: 5.0% or less, Cr / Mo≦3 being satisfied, with the remainder being Fe and unavoidable impurities; (b) the area ratio of undissolved carbides with a grain size of 0.1 μm or more on the structure surface is 1% or more; (c) having a nitride layer at least on the contact surface with the workpiece, and the hardness of the nitride layer at a depth of 25 μm from the surface is 1100 HV or more; A nitriding mold for warm and hot working is disclosed.
[0011] The same document states: (A) One of the main causes of wear in nitrided dies is that the surface layer softens due to heat generated by friction between the die surface and the high-temperature workpiece, causing plastic flow; and (B) The nitriding treatment improves the surface hardness and at the same time increases the amount of undissolved carbides, thereby synergistically improving wear caused by heat generation. is stated.
[0012] Furthermore, Patent Document 4 discloses an air-hardening cold work tool steel containing, by weight, 0.60 to 0.85% C, 0.50 to 1.50% Si, 1.70 to 2.30% Mn, 0.70 to 2.00% Cr, 0.85 to 1.50% Mo, 0.10% or less V, and the balance being Fe and impurity elements.
[0013] The same document states: (A) By reducing the C and Cr contents compared to conventional materials, the amount of carbide is reduced and the carbide grain size is refined, improving the engraving and cold hobbing properties. (B) When V is restricted to 0.10% or less, hardenability is improved, the formation of striped carbides is prevented, and engraving properties are improved; and (C) Silicon has the effect of imparting resistance to tempering softening at around 200°C. is stated.
[0014] The high toughness hot work tool steel described in Patent Document 1 has a low thermal conductivity due to a large amount of Si, and a low softening resistance due to a small amount of Mo+W / 2. In the hot work tool steel described in Patent Document 2, the Cr content is excessive, so that Cr carbides precipitate before carbides containing Mo and / or W (hereinafter, also referred to as "(Mo,W) carbides"). As a result, even though the Mo+W / 2 content is appropriate, the amount of precipitated (Mo,W) carbides decreases, and high softening resistance cannot be obtained.
[0015] The nitrided mold for warm working described in Patent Document 3, like the hot work tool steel described in Patent Document 2, does not provide high softening resistance because of the excessive Cr content. Furthermore, the air-hardening cold work tool steel described in Patent Document 4 has a low tempering softening resistance in the high temperature range exceeding 200° C. due to its small Mo+W / 2 content. [Prior art documents] [Patent documents]
[0016] [Patent Document 1] JP 2016-166379 A [Patent Document 2] JP 2008-095190 A [Patent Document 3] JP 2001-073087 A [Patent Document 4] Japanese Patent Application Publication No. 06-256895 Summary of the Invention [Problem to be solved by the invention]
[0017] An object of the present invention is to provide a die steel having high softening resistance. Another object of the present invention is to provide a die steel having high initial hardness and / or high thermal conductivity. Furthermore, another object of the present invention is to provide a die using such die steel. [Means for solving the problem]
[0018] In order to solve the above problems, the die steel according to the present invention is characterized by having the following configuration. (1) The mold steel is 0.28≦C≦0.65mass%, 0.01≦Si≦0.30mass%, 1.5≦Mn≦3.0mass%, 0.5≦Cr≦1.4mass%, 1.9≦Mo+W / 2≦4.0mass%, 0.2≦V≦1.0mass%, and 0.01≦N≦0.10mass% and the balance being Fe and unavoidable impurities. (2) The die steel, after quenching and tempering, The amount of (Mo, W) carbides with a diameter of 0.2 μm or less is 1.2 mass% or more, The (Mo, W) carbide amount / Cr carbide amount ratio (mass ratio) is 11 or more, Hardness change is 15HRC or less It consists of things. The die steel, in a state after quenching and tempering, The initial hardness is 52HRC or more, and / or Thermal conductivity at room temperature is 30W / (m K) or more. is preferred.
[0019] The die according to the present invention has the following features: (1) The die is made of the die steel according to the present invention. (2) The mold is The amount of (Mo,W) carbides having a diameter of 0.2 μm or less is 1.2 mass% or more, The (Mo,W) carbide amount / Cr carbide amount ratio (mass ratio) is 11 or more, Hardness change is 15HRC or less. The mold is The initial hardness is 52 HRC or more, and / or Thermal conductivity at room temperature is 30W / (m K) or more. is preferred. Effect of the Invention
[0020] By relatively decreasing the amount of Cr and relatively increasing the amount of Mo+W / 2, a large amount of fine (Mo,W) carbides are precipitated and the precipitation of Cr carbides is suppressed, resulting in improved softening resistance. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a schematic diagram of hat bending. [Diagram 2] 1 is a photograph showing the appearance of a punch surface that has been worn down due to hat bending. [Diagram 3] 1 is a photograph showing the appearance of a punch surface on which seizure has occurred due to hat bending. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] An embodiment of the present invention will be described in detail below. [1. Steel for molds] [1.1. Main constituent elements] The die steel according to the present invention contains the following elements, with the balance being Fe and unavoidable impurities, and includes an ingot material and a powder for additive manufacturing. The types of added elements, their component ranges, and the reasons for their limitations are as follows:
[0023] (1) 0.28≦C≦0.65mass%: C is an element necessary for obtaining high hardness. If the C content is small, the amount of dissolved C and carbide is small, and a high hardness of 52 HRC or more cannot be obtained. Therefore, the C content must be 0.28 mass% or more. The C content of the ingot material is preferably 0.50 mass% or more, and more preferably 0.55 mass% or more.
[0024] On the other hand, if the amount of C is excessive, the amount of coarse carbides increases, and the amount of retained austenite also increases, so that a high hardness of 52HRC or more cannot be obtained. Furthermore, when manufacturing a mold using an additive manufacturing method, if the amount of C is excessive, the mold is likely to crack during additive manufacturing. Therefore, the amount of C must be 0.65 mass% or less. The amount of C in the powder for additive manufacturing is preferably 0.40 mass% or less, and more preferably 0.35 mass% or less.
[0025] (2) 0.01≦Si≦0.30mass%: If the amount of Si is excessive, the thermal conductivity decreases. If the thermal conductivity decreases, the surface temperature of the die rises excessively when processing a high-temperature workpiece, and seizure tends to occur. Therefore, the amount of Si must be 0.30 mass% or less. The amount of Si is preferably 0.15 mass% or less, and more preferably 0.10 mass% or less.
[0026] (3) 1.5≦Mn≦3.0mass%: If the Mn content is too low, the hardenability decreases. Therefore, the Mn content must be 1.5 mass% or more. The Mn content is preferably 1.55 mass% or more. On the other hand, if the Mn content is excessive, the thermal conductivity decreases. Therefore, the Mn content must be 3.0 mass% or less. The Mn content is preferably 2.0 mass% or less, and more preferably 1.8 mass% or less.
[0027] (4) 0.5≦Cr≦1.4mass%: If the Cr content is too low, the hardenability decreases. Therefore, the Cr content must be 0.5 mass% or more. The Cr content is preferably 0.6 mass% or more, and more preferably 0.7 mass% or more.
[0028] On the other hand, if the Cr content is excessive, a large amount of Cr carbide is generated during tempering, and the amount of (Mo, W) carbide decreases. As a result, the softening resistance decreases. Also, if the Cr content is excessive, the thermal conductivity decreases. Furthermore, when a workpiece at high temperature is machined using a die containing excessive Cr, highly hard Cr oxides are formed on the die surface, and the oxides are caught in the die, making it more susceptible to wear. In addition, Cr oxides are formed non-uniformly on the die surface, making the workpiece (e.g., plated steel sheet) more susceptible to seizure. Therefore, the Cr content must be 1.4 mass% or less, preferably 1.3 mass% or less, and more preferably 1.2 mass% or less.
[0029] (5) 1.9≦Mo+W / 2≦4.0mass%: Mo+W / 2 contributes to high hardness and high softening resistance. If the amount of Mo+W / 2 is too small, the amount of secondary precipitated carbides will decrease, making it impossible to obtain a high hardness of 52HRC or more. The amount of (Mo,W) carbides will also decrease, lowering softening resistance. Therefore, the amount of Mo+W / 2 must be 1.9 mass% or more.
[0030] On the other hand, if the amount of Mo+W / 2 is excessive, the amount of coarse (Mo,W) carbides increases and the amount of dissolved C decreases. As a result, a high hardness of 52HRC or more and high softening resistance cannot be obtained. In addition, the amount of expensive Mo and / or W increases, so the melting cost also increases. Therefore, the amount of Mo+W / 2 must be 4.0 mass% or less. The amount of Mo+W / 2 is preferably 3.0 mass% or less, and more preferably 2.7 mass% or less.
[0031] (6) 0.2≦V≦1.0mass%: V contributes to suppressing the coarsening of crystal grains during quenching. If the V content is small, the number of pinning particles (VC particles) decreases, and the crystal grains become coarse during quenching. As a result, the toughness decreases. Therefore, the V content must be 0.2 mass% or more. The V content is preferably 0.3 mass% or more, and more preferably 0.4 mass% or more.
[0032] On the other hand, if the V content is excessive, the amount of coarse carbides that do not improve hardness increases. Also, the amount of solute C and the amount of (Mo, W) carbides decrease, so the hardness decreases and high softening resistance cannot be obtained. Therefore, the V content must be 1.0 mass% or less. The V content is preferably 0.85 mass% or less, and more preferably 0.8 mass% or less.
[0033] (7) 0.01≦N≦0.10mass%: If the N content is low, the amount of fine nitrides that become the nuclei of carbides will be small, and the specified amount of (Mo, W) carbides cannot be obtained. Therefore, the N content must be 0.01 mass% or more. On the other hand, if the N content is excessive, a large amount of coarse nitrides are generated, and fine (Mo, W) carbides cannot be obtained. Therefore, the N content must be 0.10 mass% or less. The N content is preferably 0.05 mass% or less.
[0034] (8) Inevitable impurities: In the present invention, when the contents of the following elements are less than the lower limit values, they are treated as unavoidable impurities. (a) Al<0.005mass%, (b) P<0.05mass%, (c) S<0.01mass%, (d)Cu<0.30mass%, (e)Ni<0.30mass%, (f)O<0.01mass%, (g)Co<0.10mass%, (h)Nb<0.10mass%, (i)Ta<0.10mass%, (j)Ti<0.10mass%, (k)Zr<0.01mass%, (l)B<0.001mass%, (m)Ca<0.001mass%, (n)Se<0.03mass%, (o)Te<0.01mass%, (p)Bi<0.01mass%, (q)Pb<0.03mass%, (r)Mg<0.02mass%, (s)REM<0.01mass%.
[0035] [1.2. Sub-constituent elements] The die steel according to the present invention may further contain one or more of the following elements in addition to the main constituent elements. The types of the added elements, their component ranges, and the reasons for their limitations are as follows:
[0036] (9) 0.005≦Al≦1.5mass%: (10) 0.01≦Ti≦0.5mass%: (11) 0.01≦Nb≦0.5mass%: (12) 0.01≦Zr≦0.5mass%: (13) 0.01≦Ta≦0.5mass%: Al, Ti, Nb, Zr, and Ta all contribute to suppressing the coarsening of crystal grains during quenching. All of these elements form precipitates that function as pinning particles. As a result, the crystal grains become finer and the toughness is improved. In order to obtain such effects, the contents of these elements are preferably equal to or greater than the lower limit values described above.
[0037] On the other hand, if the contents of these elements are excessive, the precipitates will aggregate and will no longer function as pinning particles, and therefore the contents of these elements are preferably equal to or less than the respective upper limits mentioned above. The die steel may contain any one of these elements, or may contain two or more of them.
[0038] (14) 0.01≦Co≦1.0mass%: Co contributes to improving high-temperature strength. To obtain such an effect, the Co content is preferably 0.01 mass% or more. The Co content is preferably 0.3 mass% or more, and more preferably 0.5 mass% or more. On the other hand, if the amount of Co is excessive, the melting cost increases and the thermal conductivity decreases. Therefore, the amount of Co is preferably 1.0 mass% or less. The amount of Co is preferably 0.9 mass% or less.
[0039] (15) 0.30≦Ni≦1.0mass%: (16) 0.30≦Cu≦1.0mass%: Both Cu and Ni retard the formation of pearlite and contribute to improving hardenability. In order to obtain such effects, the Ni content and Cu content are each preferably 0.30 mass% or more.
[0040] On the other hand, if the Ni content and Cu content are excessive, the melting cost increases and the thermal conductivity decreases. Furthermore, if the Ni content is excessive, the amount of retained austenite increases and the hardness decreases. Therefore, the Ni content and Cu content are each preferably 1.0 mass% or less. The die steel may contain either Ni or Cu, or may contain both.
[0041] (17) 0.01≦S≦0.15mass%: (18) 0.001≦Ca≦0.15mass%: (19) 0.03≦Se≦0.35mass%: (20) 0.01≦Te≦0.35mass%: (21) 0.01≦Bi≦0.50mass%: (22) 0.03≦Pb≦0.50mass%: S, Ca, Se, Te, Bi, and Pb all contribute to improving machinability. In order to obtain such effects, the contents of these elements are preferably equal to or greater than the respective lower limits mentioned above.
[0042] On the other hand, if the content of these elements is excessive, inclusions are likely to be formed. The inclusions become the starting point of fracture and cause a decrease in toughness. Therefore, the content of these elements is preferably equal to or less than the upper limit value described above. The die steel may contain any one of these elements, or may contain two or more of them.
[0043] [1.3. Characteristics] [1.3.1. Heat treatment conditions] Since the composition of the die steel according to the present invention is optimized, it exhibits high properties after quenching and tempering. Here, the "state after quenching and tempering" means (a) After soaking at 1030℃±20℃ for 45min±15min, quenching at a cooling rate of 9-30℃ / min. (b) Tempering was performed twice, by soaking at 540-600℃ for 1 hour and then cooling in air. This refers to the later state.
[0044] In addition to optimizing the components, the amount of Cr carbide and the amount of (Mo, W) carbide can be controlled by performing quenching and tempering under the conditions described above. Since crystallized carbides may occur after melting and casting, it is preferable to perform a soaking treatment at 1200°C or higher after melting and casting and before hot forging. In particular, it is preferable to perform a soaking treatment when the C content is in the range of 0.55 to 0.65 mass%. By performing a soaking treatment, it is possible to reduce coarse crystallized carbides, and in return, fine (Mo, W) carbides can be precipitated in large quantities after quenching and tempering, improving softening resistance.
[0045] If the quenching temperature is too low, the amount of solid solution elements will be small, resulting in low hardness and low softening resistance. Therefore, the quenching temperature is preferably 1010°C or higher. On the other hand, if the quenching temperature is too high, the amount of solid solution elements will be too large, the amount of retained austenite will increase, the hardness will decrease, and the crystal grains will become coarse. Therefore, the quenching temperature is preferably 1050°C or less. The holding time at the quenching temperature is preferably 45 min±15 min from the viewpoint of making the quenching temperature uniform. The cooling rate is preferably 9° C. / min or more in order to convert the structure into full martensite, and is preferably 30° C. / min or less in order to suppress quench cracks.
[0046] On the other hand, if the tempering temperature is too low, the amount of Cr carbide increases and the amount of (Mo, W) carbide decreases. Therefore, the tempering temperature is preferably 540° C. or higher. On the other hand, if the tempering temperature is too high, the carbides become coarse and the effect of improving the initial hardness and softening resistance decreases. Therefore, the tempering temperature is preferably 600° C. or less. The holding time at the tempering temperature is preferably 1 h so as to obtain the maximum hardness in terms of the temperature-time tempering parameters. The number of tempering steps is preferably two, since the structure that has been transformed from retained austenite to martensite in the first tempering step must be tempered.
[0047] [1.3.2. (Mo,W) carbide content] In the present invention, the "amount of (Mo, W) carbide" refers to the mass ratio of carbides containing Mo and / or W and having a diameter of 0.2 μm or less. The "diameter" refers to the equivalent circle diameter. Fine (Mo, W) carbides contribute to improving initial hardness and softening resistance. In general, the greater the amount of (Mo, W) carbides, the more improved the initial hardness and / or the higher the softening resistance. In order to obtain such effects, the amount of (Mo, W) carbides must be 1.2 mass% or more after quenching and tempering.
[0048] [1.3.3. (Mo,W) carbide amount / Cr carbide amount ratio] "(Mo,W) carbide amount / Cr carbide amount ratio (hereinafter also referred to as "carbide ratio")" refers to the ratio of the mass of (Mo,W) carbides having a diameter of 0.2 μm or less to the mass of Cr carbides having a diameter of 0.2 μm or less. Both fine (Mo, W) carbides and Cr carbides contribute to initial hardness. However, if the amount of Cr carbide becomes relatively excessive, the amount of (Mo, W) carbide decreases because the Cr carbide takes up C, and high softening resistance cannot be obtained. Therefore, the carbide ratio needs to be 11 or more in the state after quenching and tempering.
[0049] [1.3.4. Initial hardness] "Initial hardness" refers to the Rockwell hardness (C scale) measured at room temperature immediately after quenching and tempering. Since the die steel according to the present invention has a relatively small amount of Cr and a relatively large amount of Mo+W / 2, when quenching and tempering are performed under appropriate conditions, a large amount of fine (Mo,W) carbides are precipitated in the matrix. As a result, high initial hardness is obtained. When the manufacturing conditions are optimized, the initial hardness after quenching and tempering is 52HRC or more. When the manufacturing conditions are further optimized, the initial hardness is 53HRC or more, or 54HRC or more.
[0050] [1.3.5. Hardness change (softening resistance)] "Hardness change" refers to a value expressed by the following formula (1). Hardness change represents the magnitude of softening resistance, and the closer the hardness change is to zero, the higher the softening resistance is. Hardness change = H b -H a …(1) however, H a is the Rockwell hardness (C scale) measured at room temperature after quenching and tempering under the above conditions and then holding at 600°C for 130 hours. H b is the Rockwell hardness (C scale) measured at room temperature immediately after quenching and tempering under the above conditions.
[0051] Since the die steel according to the present invention has a relatively small amount of Cr and a relatively large amount of Mo+W / 2, when quenching and tempering are performed under appropriate conditions, a large amount of fine (Mo,W) carbides are precipitated in the matrix. The fine (Mo,W) carbides not only improve the initial hardness but also contribute to improving softening resistance. When the manufacturing conditions are optimized, the hardness change is 15HRC or less. When the manufacturing conditions are further optimized, the hardness change is 12HRC or less, or 10HRC or less.
[0052] Thermal conductivity In general, Si is added for the purposes of acting as a deoxidizer, improving hardness, improving machinability, improving oxidation resistance, improving temper softening resistance at around 200°C, etc. However, if the Si content is excessive, the thermal conductivity decreases significantly. The die steel according to the present invention has a high thermal conductivity because the amount of Si is minimized. Specifically, when the manufacturing conditions are optimized, the thermal conductivity at room temperature is 30 W / (m K) or more. When the manufacturing conditions are further optimized, the thermal conductivity is 35 W / (m K) or more.
[0053] [2. Mold] The mold according to the present invention has the following configuration. (1) The die is made of the die steel according to the present invention. (2) The mold is The amount of (Mo,W) carbides having a diameter of 0.2 μm or less is 1.2 mass% or more, The (Mo, W) carbide amount / Cr carbide amount (mass ratio) is 11 or more, Hardness change is 15HRC or less. The mold is The initial hardness is 52 HRC or more, and / or Thermal conductivity at room temperature is 30W / (m K) or more. is preferred.
[0054] [2.1. Steel for molds] The die according to the present invention is made of the die steel according to the present invention. Details of the die steel are as described above, and therefore will not be described here.
[0055] [2.3. Characteristics] The die according to the present invention can be obtained by quenching and tempering the die steel according to the present invention under predetermined conditions. Therefore, in the state after quenching and tempering, the die has the following properties: (a) The content of (Mo, W) carbides having a diameter of 0.2 μm or less is 1.2 mass% or more, (b) the (Mo,W) carbide amount / Cr carbide amount ratio (mass ratio) is 11 or more; (c) The hardness change is 15HRC or less. The mold further includes: (d) an initial hardness of 52 HRC or greater; and / or (e) Thermal conductivity at room temperature is 30 W / (m K) or more. is preferred. The details of the characteristics of the mold are as described above, so the explanation will be omitted.
[0056] [2.4. Usage] The die according to the present invention is particularly suitable as a die for hot working. Examples of applications of the die according to the present invention include a die for die casting, a die for hot stamping, and a die for tailored die quenching.
[0057] [3. Mold manufacturing method] The mold according to the present invention can be manufactured by various methods. For example, the mold according to the present invention may include: (a) Melting and casting raw materials mixed to form a desired composition; (b) A soaking treatment is performed to dissolve the precipitated carbides. (c) hot forging the ingot; (d) subjecting the hot forged product to a heat treatment for softening (e.g., spheroidizing annealing); (e) Cutting and rough machining of the softened steel material; (f) Quenching and tempering the crude product under specified conditions; (g) Finishing the heat-treated product It can be produced by the above method. The method and conditions for each step are not particularly limited, and the most suitable method and conditions can be selected depending on the purpose.
[0058] Alternatively, the mold according to the present invention comprises: (a) producing a powder of the die steel according to the present invention by an atomization method; (b) Using the obtained powder, additive manufacturing is performed. (c) Tempering the molded product In addition, if necessary, a finish process is performed after the tempering. When manufacturing a mold using additive manufacturing, by optimizing the conditions during additive manufacturing, hardening can be performed simultaneously with additive manufacturing. Other points regarding the method and conditions of each step are not particularly limited, and the most suitable method and conditions can be selected depending on the purpose.
[0059] [4. Effect] Since the amounts of added components are optimized in the die steel according to the present invention, the amounts of Cr carbide and (Mo, W) carbide can be controlled within appropriate ranges by subjecting it to appropriate heat treatment (soaking treatment and quenching / tempering treatment). As a result, the hardness change is 15HRC or less, and a die with excellent wear resistance can be obtained. Furthermore, by optimizing the components and heat treatment conditions, the initial hardness is 52HRC or more, and / or the thermal conductivity is 30W / (m·K) or more, so that the rise in die surface temperature is suppressed even when hot working is performed. As a result, softening of the die is further suppressed.
[0060] In addition, since the Cr content is relatively small, even when the die according to the present invention is applied to hot processing such as hot stamping, the generation of high-hardness Cr oxides can be suppressed. As a result, the die wear caused by high-hardness Cr oxides and the burning of the oxide film on the surface of the processed material onto the die surface can be suppressed. In addition, the high thermal conductivity is effective in shortening the cycle time. Furthermore, by adding other component elements such as Al, Co, Cu, and Ni, it is possible to further improve softening resistance, high-temperature strength, high-temperature hardenability, and machinability.
[0061] For example, if the initial hardness of a hot stamping die is low, the die will be worn during hot stamping and the die will be damaged. In addition, the temperature of the die will increase during molding, so if the softening resistance is low, the hardness will be low and wear will be promoted.
[0062] In particular, in the case of dies for tailored die quenching, the die is partially heated to slow down the cooling rate of the contact area with the heated area to a cooling rate that does not cause martensite transformation, preventing quenching of that part. Therefore, since a part of the die is exposed to high temperatures for a long time, the die needs to have high softening resistance. In addition, if the thermal conductivity of the die is low, the surface temperature of the die increases, leading to softening and wear. Also, if the thermal conductivity is low, the speed at which the die removes heat from the heated steel plate slows, and it takes time to quench the steel plate. Furthermore, it takes a long time to cool the die after the steel plate is formed and removed. If the next steel plate is formed when the die is not sufficiently cooled, the steel plate will not be sufficiently cooled and will not be quenched sufficiently.
[0063] In contrast, the die steel according to the present invention not only has high initial hardness and softening resistance, but also has high thermal conductivity, so that when this is applied to, for example, a hot stamping die or a tailored die quenching die, the forming time and the time required for cooling the die can be shortened, thereby shortening the cycle time. EXAMPLES
[0064] (Examples 1 to 26, Comparative Examples 1 to 13) [1. Sample preparation] [1.1. Examples 1 to 21 and Comparative Examples 1 to 13 (cast materials)] Steels having the chemical compositions shown in Table 1 were produced. The obtained steel ingots (except for Comparative Example 13) were subjected to a soaking treatment under the condition of uniform heating at 1240°C for 20 hours. The ingots were then hot forged to produce bars having a cross section of 55 mm x 55 mm square. The bars were then quenched and tempered. The quenching was performed by soaking at 1030°C for 60 minutes and then quenching at a cooling rate of 20 to 30°C / min. The tempering was performed by repeating twice a process of soaking at 540 to 600°C for 1 hour and then cooling in air. The tempering temperature was selected for each sample at the temperature at which the hardness was highest.
[0065] [1.2. Examples 22 to 26 (Layered Manufacturing Materials)] Powder was produced with the chemical composition shown in Table 1. The obtained powder was used for additive manufacturing to produce a bar with a cross section of 55 mm x 55 mm square. Next, the bars were tempered under the same tempering conditions as those for the ingot bars.
[0066] [Table 1]
[0067] 2. Test Method [2.1. Amount of carbide] A test piece measuring 10 mm x 12 mm x 20 mm was taken from the bar material after quenching and tempering. The total amount (mass) of carbides contained in this test piece was measured by electrolytic extraction. In addition, the electrolytically extracted carbides were automatically analyzed by SEM-EDX to measure the composition and amount (number) of each carbide with a diameter of 0.2 μm or less. Based on the obtained results, the amount of (Mo, W) carbides and the ratio of the amount of (Mo, W) carbides to the amount of Cr carbides were calculated. Those having a (Mo, W) carbide amount of 1.2 mass% or more and a (Mo, W) carbide amount / Cr carbide amount ratio of 11 or more were evaluated as "◯", and the rest were evaluated as "×".
[0068] [2.2. Initial hardness] Test pieces for measuring the initial hardness were taken from the remaining bar material after quenching and tempering, and the cross section (cross section perpendicular to the axial direction of the bar material) was flat-polished. The polished surface was used as the test surface to measure Rockwell hardness (C scale) at room temperature. When tempering was performed at temperatures ranging from 540 to 600°C, those with a maximum hardness of 52HRC or more were evaluated as "○", and others as "×".
[0069] [2.3. Softening resistance (hardness change)] The remaining bar material after quenching and tempering was heated at 600°C for 130 hours. After cooling to room temperature, test pieces for hardness measurement were taken from the remaining material and the cross section (cross section perpendicular to the axial direction of the bar material) was flat-polished. Rockwell hardness (C scale) was measured at room temperature using the polished surface as the test surface. Those whose value obtained by subtracting the hardness after heat treatment from the initial hardness was 15HRC or less were evaluated as "○", and all others were evaluated as "×".
[0070] 2.4. Thermal conductivity Test pieces for measuring thermal conductivity, measuring φ10 mm x 2 mm, were taken from the remaining bar material after quenching and tempering. Thermal conductivity at room temperature was measured using the laser flash method. Thermal conductivity at room temperature of 30 W / (m K) or more was evaluated as "○", and all other values were evaluated as "×".
[0071] 2.5. Abrasion test A punch measuring 30 mm x 60 mm x 50 mm was made from the remaining bar material after quenching and tempering. The tempering temperature was selected to be the temperature at which the initial hardness was highest. Using this punch, hat bending was performed on uncoated steel sheet heated to 920°C, and the wear of the punch was evaluated. A schematic diagram of hat bending is shown in Figure 1. First, a steel plate 14 was placed on a die 12 having a protrusion 12a, movable parts 12b, 12b arranged on the left and right of the protrusion 12a, and springs 12c, 12c supporting the movable parts 12b, 12b (Figure 1(A)). Next, a plate 16 arranged above the protrusion 12a and punches 18, 18 arranged on the left and right of the plate 16 were lowered to bend the steel plate 14 at four points (Figure 1(B)). The hat bending was an accelerated test, and the clearance was set to -15%.
[0072] A photograph of the appearance of the surface of a punch that had been worn down by hat bending is shown in Figure 2. When hat bending was performed under the above conditions, a punch that had been worn down as shown in Figure 2 within 90 shots was evaluated as "X", and a punch that did not have this wear down was evaluated as "O".
[0073] [2.6. Burn test] A punch was prepared in the same manner as in the wear test. Using this punch, hat bending was performed on an aluminum-plated steel sheet heated to 920° C. The clearance was set to −30%. A photograph of the appearance of the surface of a punch on which seizure occurred due to hat bending is shown in Figure 3. When hat bending was performed under the above conditions, punches on which seizure as shown in Figure 3 occurred within 90 shots were evaluated as "X", and punches on which seizure did not occur were evaluated as "O".
[0074] [3. Results] The results are shown in Table 2. From Table 2, the following can be seen. (1) Comparative Example 1 has low initial hardness, large hardness change, and low wear resistance. This is believed to be due to the low C content and the small amount of fine carbides. (2) Comparative Example 2 has low initial hardness, large hardness change, and low wear resistance. This is believed to be due to the excessive C content and the large amount of coarse carbides. (3) Comparative Example 3 exhibited a large change in hardness, a low thermal conductivity, a low wear resistance, and a low seizure resistance. This is believed to be due to the low thermal conductivity caused by the high Si content, and the small amount of fine (Mo, W) carbides caused by the high Cr content.
[0075] (4) Comparative Example 4 has a large hardness change, a low thermal conductivity, a low wear resistance, and a low seizure resistance. This is believed to be due to the high C and Cr contents, which results in a small amount of fine (Mo, W) carbides and an excessive Mn content. (5) Comparative Example 5 has a large hardness change, a low thermal conductivity, a low wear resistance, and a low seizure resistance. This is believed to be due to the fact that the Cr content is high, resulting in a small amount of fine (Mo, W) carbides. (6) Comparative Example 6 has a large hardness change, a low thermal conductivity, a low wear resistance, and a low seizure resistance. This is believed to be due to the fact that the Cr content is even more excessive than in Comparative Example 5.
[0076] (7) Comparative Example 7 has a large hardness change, a low thermal conductivity, a low wear resistance, and a low seizure resistance. This is believed to be due to the fact that the Cr content is even more excessive than in Comparative Example 5. (8) Comparative Example 8 has low initial hardness, large hardness change, and low wear resistance. This is believed to be due to the low amount of Mo+W / 2. (9) Comparative Example 9 has low initial hardness, large hardness change, low thermal conductivity, low wear resistance, and low seizure resistance. This is believed to be due to the excessive amount of Mo+W / 2, which results in coarse carbides.
[0077] (10) Comparative Example 10 has low initial hardness, large hardness change, and low wear resistance. This is believed to be due to the excessive amount of V and the small amount of dissolved C and fine (Mo, W) carbides. (11) Comparative Example 11 has a large hardness change and low wear resistance. This is believed to be due to the small amount of N. (12) Comparative Example 12 had a large change in hardness and low wear resistance. This is believed to be due to the excessive N content. (13) Comparative Example 13 has low initial hardness, large hardness change, and low wear resistance. This is believed to be because no soaking treatment was performed, so coarse crystallized carbides remained, and the amount of dissolved C and fine (Mo, W) carbides were small. (14) In all of Examples 1 to 26, the initial hardness was 52HRC or more, the hardness change was 15HRC or less, and the thermal conductivity at room temperature was 30W / (m·K) or more. In addition, the wear resistance and seizure resistance were also excellent. Therefore, if this is applied to, for example, a hot stamping die, the wear resistance can be improved.
[0078] [Table 2]
[0079] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the gist of the present invention. [Industrial Applicability]
[0080] The die steel according to the present invention can be used as a material for die casting dies, hot stamping dies, tailored die quench dies, and the like.
Claims
1. Mold steel having the following composition: (1) The mold steel is 0.28≦C≦0.65 mass%, 0.01≦Si≦0.30 mass%, 1.5≦Mn≦3.0mass%, 0.5≦Cr≦1.4mass%, 1.9≦Mo+W / 2≦4.0mass%, 0.2≦V≦1.0 mass%, and 0.01≦N≦0.10mass% and the balance being Fe and unavoidable impurities. (2) The die steel, in a state after quenching and tempering, The amount of (Mo, W) carbide is 1.2 mass% or more, The (Mo,W) carbide amount / Cr carbide amount ratio (mass ratio) is 11 or more, Hardness change is 15HRC or less It consists of things. however, The "state after quenching and tempering" means A soaking treatment is performed on the ingot at a temperature of 1200°C or more, and the soaked ingot is hot forged to obtain a crude product, (a) After soaking at any temperature of 1030°C ± 20°C for any time of 45 min ± 15 min, quenching at any cooling rate of 9 to 30°C / min; (b) Tempering was performed twice by soaking at a temperature of 540 to 600 ° C for 1 h and then cooling in air. This refers to the later state. The "(Mo,W) carbide amount" refers to the mass ratio of carbides containing Mo and / or W and having a diameter of 0.2 μm or less, The "(Mo,W) carbide amount / Cr carbide amount ratio (mass ratio)" refers to the ratio of the mass of (Mo,W) carbides having a diameter of 0.2 μm or less to the mass of Cr carbides having a diameter of 0.2 μm or less, The "diameter" refers to the equivalent circle diameter. The "hardness change" refers to a value represented by the following formula (1). Hardness change=H b −H a (1) however, H a is the Rockwell hardness (C scale) measured at room temperature after quenching and tempering under the above conditions and then holding at 600° C. for 130 hours; H b is the Rockwell hardness (C scale) measured at room temperature immediately after quenching and tempering under the above conditions.
2. 0.005≦Al≦1.5mass%, 0.01≦Ti≦0.5mass%, 0.01≦Nb≦0.5mass%, 0.01≦Zr≦0.5 mass%, and 0.01≦Ta≦0.5mass% The die steel according to claim 1, further comprising one or more elements selected from the group consisting of:
3. 0.01≦Co≦1.0mass% The die steel according to claim 1 or 2, further comprising:
4. 0.30≦Ni≦1.0 mass%, and / or 0.30≦Cu≦1.0mass% The die steel according to any one of claims 1 to 3, further comprising
5. 0.01≦S≦0.15mass%, 0.001≦Ca≦0.15 mass%, 0.03≦Se≦0.35 mass%, 0.01≦Te≦0.35 mass%, 0.01≦Bi≦0.50 mass%, and 0.03≦Pb≦0.50mass% The die steel according to any one of claims 1 to 4, further comprising one or more elements selected from the group consisting of:
6. A mold steel described in any one of claims 1 to 5, which has an initial hardness of 52 HRC or more after the quenching and tempering. Here, the "initial hardness" refers to the Rockwell hardness (C scale) measured at room temperature immediately after the quenching and tempering.
7. A mold steel described in any one of claims 1 to 6, which has a thermal conductivity of 30 W / (m·K) or more at room temperature after the quenching and tempering.
8. A mold having the following configuration: (1) The die is made of the die steel according to any one of claims 1 to 7. (2) The mold is The amount of (Mo, W) carbide is 1.2 mass% or more, The (Mo,W) carbide amount / Cr carbide amount ratio (mass ratio) is 11 or more, The hardness change is 15 HRC or less.
9. 9. The mold according to claim 8, wherein the initial hardness is 52 HRC or more. Here, the "initial hardness" refers to the Rockwell hardness (C scale) measured at room temperature immediately after the quenching and tempering.
10. 10. The mold according to claim 8 or 9, having a thermal conductivity of 30 W / (m·K) or more at room temperature.
Citation Information
Patent Citations
High-temperature, high-strength and low-carbon hot work die steel and preparation method thereof
CN109487166A
Air-hardened cold tool steel
JP1994256895A
Die excellent in heat resistance, and its manufacture
JP2000248332A
Nitrided die for warm and hot working, excellent in wear resistance
JP2001073087A
Hot-working tool steel having superior toughness and high-temperature strength, and production method therefor
JP2008095190A